UiTM Mukah Bulletin: Inou Dengah UiTM Mukah? 3rd Issue Volume 2 October 2024 / UiTM Cawangan Sarawak Kampus Mukah - UiTM Cawangan Sarawak, Kampus Mukah (Corporate Communication Unit, UiTM Mukah Campus, 2024)
It is delighted to acknowledge the editorial team’s diligent efforts in successfully releasing the Third Edition (Volume 2) of Inou Dengah UiTM Mukah?. Congratulations to the editorial team, who put extra effort into ensuring everything went smoothly. It is an honour to witness the launch of this latest edition of our campus bulletin, a testament to the team’s dedication to quality and excellence. Inou Dengah UiTM Mukah? serves as an excellent platform for staff members to refine their writing skills and express their thoughts creatively. It serves as a space for them to showcase their ability to communicate ideas effectively and engage meaningfully with readers. Despite the challenge of balancing numerous professional responsibilities, the editorial team has demonstrated exceptional commitment, resilience, and perseverance. Their capacity to maintain focus and dedication amidst demanding schedules is truly admirable and reflects their professionalism and teamwork. The dedication they have shown in bringing this edition to fruition deserves the highest praise. Congratulations to all the authors who contributed their insightful articles to this volume, and heartfelt appreciation to the entire editorial team for a job exceptionally well done. Your efforts have once again made Inou Dengah UiTM Mukah? a remarkable publication that upholds the values and excellence of our campus.